PENGEMBANGAN LKPD BERBANTUAN APLIKASI CANVA PELAJARAN MATEMATIKA MATERI BANGUN RUANG SISWA KELAS IV SD - Anggraini, Monalika; Surmilasari, Nora; Jayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problems in this study include three main things, namely: (1) how to develop a valid Canva application-assisted LKPD on mathematics subjects on spatial geometry material for grade IV elementary school students; (2) how to develop the LKPD so that it is practical to use in learning; and (3) what is the final result of the Canva application-assisted LKPD that has been developed. This study uses the type of development research (Research and Development/R&D), with the development procedure referring to the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in this study were carried out through observation, questionnaires, tests, and documentation. The results of the study showed that the LKPD developed was declared very valid based on the validation results from experts in the fields of media, language, and materials, with a percentage of 94%. In terms of practicality, the results were 81% at the one-to-one trial stage and 85% at the small group trial stage, based on the questionnaire filled out by students. This shows that the LKPD is classified as very practical to use in learning. Meanwhile, from the aspect of effectiveness, a percentage of 95% was obtained, which is included in the very effective category. This data was obtained from the results of student work on questions, where 19 out of 20 students achieved the Learning Objective Achievement Criteria (KKTP) with a value range of 61 to 80. This finding shows that students are very enthusiastic in using teaching materials in the form of LKPD assisted by the Canva application in learning mathematics on spatial geometry material in grade IV of elementary school.